1958
DOI: 10.1002/ange.19580701106
|View full text |Cite
|
Sign up to set email alerts
|

4‐Desoxy‐humulon, ein neuer Hopfenbitterstoff

Abstract: auf Stärke, Auffangen der durch Abklatsch lokalisierten Zone im Glaspulverbett und Elution mit wenig Wasser eine Aktivitätsausbeute von 55% und eine Proteinausbeute von 60% erhalten.Es wird sich deshalb oft lohnen unter Preisgabe eines Teils der Aktivität ein Enzym von anderen Eiweißkörpern elektrophoretisch zu trennen. In gewissen Fällen wird der weniger schädliche TRIS-Citrat-Puffer, bei dem am Ende der Stärkeelektrophorese aus dem Glaspulver 85% der Enzymaktivität wiedergewonnen wurden, oder eine weitere no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…These results do not lend support to the view that the a acids are formed by oxidation (or photolysis) of the ß acids (33,371,404,406) but rather that the a and ß acids are formed from a common precursor. Support for the latter view came with the isolation of desoxyhumulone (XXXV) from hops (292,293). Oxidation of this compound affords humulone while condensation with a further isoprene residue gives lupulone.…”
Section: Development and Biogenesis Of Hop Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results do not lend support to the view that the a acids are formed by oxidation (or photolysis) of the ß acids (33,371,404,406) but rather that the a and ß acids are formed from a common precursor. Support for the latter view came with the isolation of desoxyhumulone (XXXV) from hops (292,293). Oxidation of this compound affords humulone while condensation with a further isoprene residue gives lupulone.…”
Section: Development and Biogenesis Of Hop Constituentsmentioning
confidence: 99%
“…Five years later 4-desoxyhumulone was obtained crystalline, mp 83°, and characterized as the tribenzoate, mp 139° ( 292). Subsequently, it was isolated from Hallertau hops (1957 crop) in 0.02% yield (293). In the following years the yields were: 1958, 0.038%; 1959, 0.05% (210).…”
Section: -Desoxyhumulonementioning
confidence: 99%
“…It is clearly desirable for economic dcsoxycohumulone (III, R = Pr1) is also of reasons to know when the optimum available interest because of the probable interrelation yield of a-acids (I) is attained, but a know-of these compounds in a-acid biosynthesis, ledge of the relative rates of development of It has been suggested81Mfi that p-acids (II) humulone (I, R = Bu1) cohumulone (I, are formed before the a-acids (I) and that the R = Pr1) adhumulone (I, R = scc-Bu) latter compounds are produced at the vXL expense2 of the j3-acids (II) and stimulated by sunlight. [8][9][10][11][12][13] However more recent work0 has shown that cc-acids (I) and /3-acids (II) appear simultaneously in the hops from a very early stage of development, and that their rates of development are similar throughout. In addition, it has been shown8 by gas-liquid-chromatography (GLC) of the different acyl side-chain (R) derivatives that the proportions of cohumulone (I, R = Pr1) in the oc-acids (I) and colupulone (II, R = Pr1) in the /}-acids increase concurrently, reaching steady proportions some time before the hops are fully ripe.…”
Section: Introductionmentioning
confidence: 99%